Spontaneous grafting of nitrobenzenediazonium salt on plasma-modified copper substrates - Su, Jiangling; Muhle, Marius; Nembot, Nelly; Prüßner, Tim; Xie, Xiaofan; Wittstock, Gunther; Grundmeier, Guido (Electrochimica Acta)

Interface and volume transport on technical cataphoretic painting: A comparison of steel, hot-dip galvanised steel and aluminium alloy - Reichinger, M.; Bremser, Wolfgang; Dornbusch, M. (Electrochimica Acta)

Combined Electrochemical and Electron Spectroscopic Investigations of the Surface Oxidation of TiAlN HPPMS Hard Coatings - Wiesing, Martin; to Baben, Moritz; Schneider, Jochen M.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Electrochimica Acta)

Capacitance performance of cobalt hydroxide-based capacitors with utilization of near-neutral electrolytes - Fedorov, Fedor S.; Linnemann, Julia; Tschulik, Kristina; Giebeler, Lars; Uhlemann, Margitta; Gebert, Annett (Electrochimica Acta)
Conventional alkaline solutions used for capacitive performance of electrodeposited cobalt hydroxides have a number of disadvantages as they are corrosive, environmentally unfriendly and provide a small working potential range. In this study, the capacitive properties of electrodeposited cobalt hydroxide/oxide were investigated in 1 M Na2SO4 solution with pH 5.5 by means of cyclic voltammetry, galvanostatic charging/discharging experiments and electrochemical impedance spectroscopy. The capacitance of the cobalt hydroxide/oxide was demonstrated to have high values of 141 F g−1 at scan rate 8 mV s−1 in this 1 M Na2SO4 solution. The anodic potential range is extended by 0.8–1.3 V vs. Ag/AgCl. A good cyclic stability and reversibility were observed.
Keywords: electrodeposition; cobalt hydroxide; supercapacitors